PTEN Hamartoma Tumor Syndrome: Skin Manifestations and Insights Into Their Molecular Pathogenesis - Innella, Giovanni; Bonora, Elena; Neri, Iria; Virdi, Annalucia; Guglielmo, Alba; Pradella, Laura Maria; Ceccarelli, Claudio; Amato, Laura Benedetta; Lanzoni, Anna; Miccoli, Sara; Gasparre, Giuseppe; Zuntini, Roberta; et al. (Frontiers in Medicine, 2021)
Germline PTEN pathogenic variants cause a spectrum of disorders collectively labeled PTEN Hamartoma Tumor Syndrome (PHTS) and featured by hamartomas, developmental anomalies and increased cancer risk. Studies on experimental models provided evidence that PTEN is a “haploinsufficient” tumor-suppressor gene, however, mechanisms involved in the pathogenesis of clinical manifestations in PHTS patients remain elusive. Beyond analyzing clinical and molecular features of a series of 20 Italian PHTS patients, we performed molecular investigations to explore the mechanisms involved in the pathogenesis of PTEN-associated manifestations, with special focus on mucocutaneous manifestations. Typical mucocutaneous features were present in all patients assessed, confirming that these are the most important clue to the diagnosis. The most frequent were papules located in the trunk or extremities (73.7%), oral mucosa papules (68.4%), acral/palmoplantar keratosis and facial papules (both 57.9%), according with literature data. Molecular analyses on one trichilemmoma suggested that the wild-type PTEN allele was retained and expressed, reinforcing the evidence that PTEN does not require a second somatic hit to initiate pathogenic processes. Unexpectedly, one patient also displayed a cutaneous phenotype consistent with atypical mole/melanoma syndrome; no variants were detected in known melanoma genes, but Whole Exome Sequencing showed the rare truncating variant c.495G>A in the CDH13 gene that might have cooperated with PTEN-haploinsufficiency to generate such phenotype. Our findings confirm the reproducibility of known PHTS manifestations in real-world practice, highlighting the role of mucocutaneous manifestations in facilitating prompt diagnosis of the syndrome, and provide some insights into the pathogenic process induced by PTEN alterations, which may contribute to its understanding.